The Effect of Modelling the Way Strategy on Students’ Writing Procedure Text Ability at the Eleventh Grade of MAS Al-Abraar Siondop Julu in 2020/2021 Academic Year - amelia rahmadani lubis (JURNAL LINER (Language Intelligence and Educational Research), 2021)
ABSTRACT: The result of this research: 1) The application of modelling the way strategy on students can be seen from 16 aspects observed by the observer the total score was 48 and the average was 3 it was “Good” categorized. It mean that the writer using modelling the way strategy on writing procedure text is well, 2) The students writing procedure text before and after using modelling the way strategy. It can be seen from the students’ frequency before using modelling the way strategy was on 44.09 or 10 students, it was categories “Fail” and after using modelling the way strategy was 69.13 or 9 students, these were categories “Enough”, 3) There is any significant effect of modelling the way strategy on students writing procedure text ability. Normality test shows that sig value 0.039>0.05 pretest and posttest 0.027>0.05. Homogeneity Test shows that the value of (Sig.) of the pretest 0.346>0.05 it means that the sample variances is homogenuous. Pair sample ttest that significant value was less than 0.05 (0.000<0.05). So, Ha is accepted. It means that there is any significant of using modelling the way strategy on students writing procedure text ability at the eleventh grade of MAS Al-Abraar Siondop Julu. Keywords: Modelling the Way, Strategy, Writing, Procedure Text